Effects of Pre-Cutting Round Alfalfa Hay Bales on Forage Quality and Processing Time - W. E. Brown; E. Harms; J Heimsoth; J. McGinnis; C. I. Vahl; B. J. Bradford; M. J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2020)
Round hay balers with knives that cut the hay as it enters the baling chamber reduce the particle size upon baling, and eliminate the need for a tub grinder. The objective of this study was to evaluate the effects of a round hay baler with knives on forage quality of alfalfa hay at baling and after storage, and the effects of the processing method on nutrient composition and particle size distribution. Alfalfa hay was baled (560 M Megawide HC2, John Deere, Moline, IL) with knives every 4 inches (CUT; theoretical length of cut) or without knives (NORM). At baling and after 6 months of uncovered storage, bales were weighed, measured, and 10 core samples were obtained for nutrient analysis. Cores were separated into outer 6 inches and inner 6- to 18-inch segments to determine the depth of spoilage. After storage, particle size was reduced to approximately 4 inches using a mixer wagon for CUT (CUT-MIX) or a tub grinder for NORM (NORM-GRIND). Compared with NORM, CUT increased bale weight and density. Core depth interacted with storage timepoint whereby acid detergent fiber (ADF) concentration increased more for outer than inner cores from baling to the end of storage, with similar effects for lignin and 240-hour undigestible NDF. Compared with NORM, CUT increased concentrations of aNDF organic matter, ADF, and lignin, and decreased relative forage quality (RFQ). The CUT-MIX treatment increased time to reduce particle size, but decreased processing shrink by 6.1% compared with NORM-GRIND. Additionally, when compared with NORM-GRIND, CUT-MIX increased fiber content and decreased fiber digestibility, which may have been due to sampling error from longer particle size. In summary, CUT produced larger, more dense bales and increased fiber content slightly, and CUT-MIX decreased processing shrink but increased fiber content with additional longer particles after processing, which could be advantageous for physically effective fiber in ruminant diets. Further work should continue to evaluate leaf loss during baling, and options for processing and incorporating pre-cut hay into diets.
Keywords: density; shrink; round bale; particle size; grinding